AN ANALYSIS OF MAIN CHARACTER â€œJACE WAYLANDâ€ IN CASSANDRA CLAREâ€™S NOVEL, THE MORTAL INSTRUMENTS CITY OF GLASS - Yarni Oktaria; yuniarti Yuniarti; Sarair Sarair (Fakultas Agama Islam Universitas Muhammadiyah Aceh, 2017)
This research discusses about a main character in the Cassandra Clareâ€™s Novel which entitled The Mortal Instruments, City of Glass. The writer analyzes how the main character solves problem that he has in his life. The design of this writing is qualitative method focusing on library research. This research uses personality traits adapted from Hans Eysenck and other theories that identified from habit, behavior, action and attitude. To analyze all the sentences in the novel which related to behavior and action of the main character, the writer uses content analysis. The result of this analysis shows that many positive sides of the character that can be adapted by the readers. After all, Jace Wayland described as someone who has rude and selfish (Psychoticism), a calm person (Extraversion), and an impulsive and unstable emotional (Neuroticism), fightful and struggle to save people whom he loveand to solve his problems in his life.